Disk Battery Ingestion A Malpractice Case that Results in Pneumonia - Şarkış, Cihat; Yazıcı, Selçuk; Can, Muhammet (The Bulletin of Legal Medicine, 2016)
Alkaline batteries have become the second most swallowed foreign bodies following coins. Most cases have an uncomplicated course, but some may lead to serious complications and even death.Here we report a 28 months old boy who had experienced discomfort, eating refusal, vomiting and slightly wheezing after falling from a sofa bed. He has been in three different county hospitals and two private hospitals due to complaints, has been examined by two pediatricians and a cranial surgeon. A cranial CT imaging, a cranial X-ray radiograph and a chest X-ray radiograph was obtained. Firstly, diagnosed as head and neck trauma, then diagnosed as acute bronchiolitis, and finally pneumonia. Hospitalized twice. Finally, a chest radiograph revealed a button battery in the esophagus. The foreign body was endoscopic removed. The child had a quick clinical impairment after removal of the battery.As a result, alkaline batteries with their increasing risk of engulfment poses very serious problems. The parents and physicians should be informed against increasing frequency of ingestion of alkaline batteries by infants and children. Also, clinicians should be careful about the risk of these batteries that they can cause pneumonia and infiltration which may make it difficult to detect the foreign body.
Keywords: disk batteries; pneumonia